2012
DOI: 10.1097/tp.0b013e318265c508
|View full text |Cite
|
Sign up to set email alerts
|

Combined Liver-Intestine Grafts Compared With Isolated Intestinal Transplantation in Children

Abstract: Risk of mortality at 6 months after intestinal transplantation increased when the liver is included as combined graft. Strategies to reduce mortality such as refining selection for transplantation and early referral before the development of liver failure should be a priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…recently reported a prospective analysis of 51 children with intestinal failure who underwent transplantation, 39 of whom received combined liver and small bowel grafts. Mortality at 6 months after transplantation was 19%, all in the combined liver-small bowel transplantation group 49 . Similarly, Grant et al reported increased mortality one year after combined liver/small bowel transplantation than isolated small bowel (77% versus 60%, p <0.001) 50 .…”
Section: Discussionmentioning
confidence: 96%
“…recently reported a prospective analysis of 51 children with intestinal failure who underwent transplantation, 39 of whom received combined liver and small bowel grafts. Mortality at 6 months after transplantation was 19%, all in the combined liver-small bowel transplantation group 49 . Similarly, Grant et al reported increased mortality one year after combined liver/small bowel transplantation than isolated small bowel (77% versus 60%, p <0.001) 50 .…”
Section: Discussionmentioning
confidence: 96%
“…Surgical difficulties on wall closure and vascular complications as cause of early death or graft failure almost disappeared with the staged abdominal closure technique from the 2000s . Biliary complications were not totally prevented by the “en bloc” technique of L‐SBTx.…”
Section: Discussionmentioning
confidence: 99%
“…The historic incidence of ACR (80%) has improved to 20-50% (6,(8)(9)(10)(11). The level of ACR has declined following the use of rATG (4,12). We used rATG and steroids for induction therapy and our ACR rate was 57%.…”
Section: Discussionmentioning
confidence: 96%